Metaphysics and hermeneutics in the Medieval Platonic tradition - Gersh, Stephen, author.
1 online resource.
Keywords: "The origins of what might be called 'the dynamic relation between metaphysics and hermeneutics' and which forms the primary subject matter of the present volume are buried in the mists of history. Nevertheless, the phenomenon is fully visible at the point where the Stoic allegorical technique that had developed during the Hellenistic era of antiquity was adopted by the Platonists. How much further back the twofold root of metaphysics and hermeneutics can be traced remains an open question, given that the problem itself is of a hermeneutical and perhaps even metaphysical nature, and given that we can never escape from this circularity. The thirteen essays in this volume all in various ways to the understanding of the chosen topic. When the first essays were written, the topic itself was only partially articulated, whereas some of the later pieces were composed with a more conscious awareness of its ramifications. For this reason, it seemed best to supplement the original texts with an introduction that is more fully developed than would normally be the case with a collective volume and indeed adopts a certain meta-critical stance"--